Analysis of the Application of the Capital Asset Pricing Model (CAPM) Method in Making Islamic Stock Investment Decisions - Ramli, Anwar; Anwar, Indah Lestari (Golden Ratio of Finance Management, 2024)
This study aims to analyze the application of the Capital Asset Pricing Model (CAPM) in sharia stock investment decision making, especially JII70. The research design used is a quantitative approach. The type of research used is descriptive research. This research leads to the shares of companies included in the Jakarta Islamic Index 70 (JII70) on the Indonesia Stock Exchange. The population in this study were all shares of companies listed on the Jakarta Islamic Index 70 (JII70) in the period January 2019-January 2024. The research sample was 32 JII70 stock issuers who consistently entered JII70 during the period January 2019-January 2024. The results showed that there were 14 issuers of JII70 stocks in the efficient category because they had individual stock returns greater than the expected rate of return [Ri > E(Ri)] with positive individual returns.